2013
DOI: 10.1002/j.2161-1939.2013.00039.x
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evidence for the Importance of Conceptualizing Client Strengths

Abstract: Case conceptualizations from 120 counselors-in-training and post-master's-level

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In fact, one study found that intake forms that utilized solution-focused language regarding the purpose of the visit appeared to create hope and promote pretreatment changes on their own (Richmond et al, 2014). The psychologist’s ability to identify client strengths and incorporate them into conceptualization are related to improved treatment outcomes, improved therapeutic relationship, and improved counselor perceptions of counseling efficacy (Welfare et al, 2013).…”
Section: Lgbtq+ Mental Healthmentioning
confidence: 99%
“…In fact, one study found that intake forms that utilized solution-focused language regarding the purpose of the visit appeared to create hope and promote pretreatment changes on their own (Richmond et al, 2014). The psychologist’s ability to identify client strengths and incorporate them into conceptualization are related to improved treatment outcomes, improved therapeutic relationship, and improved counselor perceptions of counseling efficacy (Welfare et al, 2013).…”
Section: Lgbtq+ Mental Healthmentioning
confidence: 99%